The forgotten Alcott : essays on the artistic legacy and literary life of May Alcott Nieriker - Flint, Azelina; Hehmeyer, Lauren (New York : Routledge, 2022)
"This collection is the first academic study of the captivating life and career of expatriate artist, writer and activist, May Alcott Nieriker. Nieriker is known as the sister of Louisa May Alcott and model for "Amy March" in Alcott's Little Women. As this book reveals, she was much more than "Amy"--she had a more significant impact on the Concord community than her sister, and later became part of the creative expat community in Europe. There, she imbued her painting with the abolitionist activism she was exposed to in childhood and pursued an ideal of artistic genius that opposed her sister's vision of self-sacrifice. Embarking on a career that took her across London, Paris, and Rome, Nieriker won the acclaim of John Ruskin and forged a network of expatriate female painters who changed the face of nineteenth-century art, creating opportunities for women that lasted well into the twentieth century. A "Renaissance woman," Nieriker was a travel writer, teacher, and curator. She is recovered here as a transdisciplinary subject who stands between disciplines, networks, and ideologies-stiving to recognize the dignity of others. Contributors include foundational Alcott scholar, Daniel Shealy and Pulitzer Prize winner, John Matteson, as well as Curators, Jan Turnquist (Orchard House) and Amanda Burdan (Brandywine River Museum of Art). In this book, readers will become acquainted with a dynamic feminist thinker who transforms our understanding of the place of women artists in the wider cultural and intellectual life of nineteenth-century Britain, France, and the United States"--
Introduction by Azelina Flint -- Chapter 1 "Concordia's Queen": May Alcott and the Town of Concord by Daniel Shealy -- Chapter 2 "Successive chapters in a romance": May Alcott Nieriker's influence on the development of the woman artist in Louisa May Alcott's fiction by Azelina Flint -- Chapter 3 "Little Rafael" -- May Alcott Nieriker's beginnings -- A biographical sketch by Susan Bailey -- Chapter 4 Armed with a Brush: May Alcott Nieriker as a representative woman artist in Paris by Lauren Hehmeyer -- Chapter 5 Alone Together in Paris: May Alcott Nieriker and Rosa Peckham Danielson by Amanda C. Burdan -- Chapter 6 Republics Abroad: The Art and Politics of Margaret Fuller and May Alcott Nieriker in Nineteenth Century Europe by Ariel Clark Silver -- Chapter 7 "Disciplinary Conversations": May Alcott Nieriker's "An Artist's Holiday" by Marlowe Daly-Galeano -- Chapter 8 An Ideal Life: May Alcott Nieriker, Tourism, and Life Abroad by Kristi Lynn Martin -- Chapter 9 "Let the World Know You Are Alive" May Alcott Nieriker and Louisa May Alcott Confront Nineteenth-Century Ideas about Woman's Genius by Lauren Hehmeyer -- Chapter 10 Black Subjectivity in the Life and Art of May Alcott Nieriker by Julia K. Dabbs -- Chapter 11 "The Pure Hope of Giving ... Pleasure": May Alcott, John Ruskin and the Moral Aesthetic by John Matteson -- Chapter 12 The "Precious Legacy" of May Alcott Nieriker: Her Paintings and her Child by Jan Turnquist -- Conclusion No Longer Forgotten by Lauren Hehm
Keywords: Alcott, May, -- 1840-1879 -- Criticism and interpretation; Alcott, Louisa May, -- 1832-1888 -- Family; Women artists -- United States -- Biography; Expatriate artists -- Europe -- History -- 19th century; Americans -- Europe -- History -- 19th century; LITERARY CRITICISM / General